The use of anti-interleukin-1 agents and tumor necrosis factor‐alpha inhibitors in renal transplant recipients - Veli Yazısız,; Vural Taner Yılmaz,; İsmail Uçar,; Özgür Dandin,; Bengisu Aslan,; Funda Erbasan,; Hüseyin Koçak,; Mustafa Ender Terzioğlu, (Archives of Rheumatology, 2021)
Objectives: The aim of this study was to investigate the efficacy and safety of anti-interleukin-1 (anti-IL-1) agents and tumor necrosis factor‐alpha (TNF-α) inhibitors in renal transplant patients. Patients and methods: Between February 2014 and February 2020, data of 12 renal transplant recipients (9 males, 3 females; median age: 51 years; range, 19 to 70 years) who received anti-IL-1 agents or TNF-α inhibitors for inflammatory diseases in the post-transplant time period and were followed in a single transplant center (n=12) were retrospectively analyzed. A total of 46 cases were reported in the literature, before the data were collected. The overall outcomes of all cases were analyzed in this study. Results: Thirty-seven patients received anti-IL-1 agents in the post-transplant period. The main indications for anti-IL-1 agents were familial Mediterranean fever (FMF) and amyloidosis (75.7%). The continuation rate of colchicine treatment in patients with FMF was 85.7%. Anti-IL-1 agents prevented attacks completely in 89.3% of FMF patients. The number of cases used TNF-α inhibitors among renal transplant patients was lower (n=21). The TNF-α inhibitors were used mainly for inflammatory bowel diseases (57.1%) and ankylosing spondylitis (33.3%) and suppressed the disease activity in most of the patients with inflammatory diseases (72.7%). Death (n=3) and malignancies (n=3) were reported in patients who received TNF-α inhibitors, but not in patients who received anti-IL-1. The renal outcomes and graft survival rates were satisfactory in patients who received both anti-IL-1 agents and TNF-α inhibitors. Conclusion: Our results support that anti-IL-1 agents can be used effectively and safely in renal transplant patients.